The Role of Innovation Ambidexterity in Enhancing MSME Performance: Insights from the Fashion Industry - Sheila Frizqia Jelita; Ruslan Prijadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the influence of leadership characteristics and intellectual resources on organizational performance through innovation ambidexterity mediation in MSMEs in the fashion industry in Bandung. In a competitive environment, MSMEs need to adopt explorative and exploitative innovations to achieve optimal performance. The results show that adaptive leadership and risk tolerance support Combined Innovation Ambidexterity (CIA), which has a positive impact on MSME performance, while Balanced Innovation Ambidexterity (BIA) is less relevant. Intellectual resources (human, structural, and relational) also play a significant role in driving MSME innovation and performance. This study recommends the development of adaptive leadership, increasing risk tolerance, and managing intellectual resources effectively to help MSMEs become more competitive through flexible innovation strategies. The CIA approach allows MSMEs to adapt to market changes and provides new contributions to the innovation ambidexterity literature.